2021
DOI: 10.1073/pnas.2101062118
|View full text |Cite
|
Sign up to set email alerts
|

Task complexity moderates group synergy

Abstract: Complexity—defined in terms of the number of components and the nature of the interdependencies between them—is clearly a relevant feature of all tasks that groups perform. Yet the role that task complexity plays in determining group performance remains poorly understood, in part because no clear language exists to express complexity in a way that allows for straightforward comparisons across tasks. Here we avoid this analytical difficulty by identifying a class of tasks for which complexity can be varied syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 55 publications
(72 reference statements)
2
35
0
Order By: Relevance
“…Finally, we note that we only studied one class of tasks: numerical estimation with a non-negative, objective truth. Relevant research on other classes of tasks has similarly demonstrated that variation in context features, such as complexity 33 38 , fundamentally alter collective problem-solving outcomes. Also worth noting is our focus on tasks involving social influence when, in reality, we should not rule out the possibility that simply aggregating individuals’ pre-influence estimates might be an appropriate, costless solution for some situations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we note that we only studied one class of tasks: numerical estimation with a non-negative, objective truth. Relevant research on other classes of tasks has similarly demonstrated that variation in context features, such as complexity 33 38 , fundamentally alter collective problem-solving outcomes. Also worth noting is our focus on tasks involving social influence when, in reality, we should not rule out the possibility that simply aggregating individuals’ pre-influence estimates might be an appropriate, costless solution for some situations.…”
Section: Discussionmentioning
confidence: 99%
“…The nature and complexity of the problem to be overcome determines whether quick dissemination of partial solutions or improvements through efficient networks is most beneficial to the group. Generally, groups solve problems more efficiently than individuals (Mason and Watts 2012), as long as the task is complex enough to warrant organizational efforts in allocating tasks and assembling results (Almaatouq et al 2021). Well-connected groups find good solutions faster than sparsely connected groups (Derex and Boyd 2016;Lazer and Friedman 2007), as incremental improvements spread quickly and are adopted by most of the group.…”
Section: Q5 What Population-level Characteristics Affect the Degree O...mentioning
confidence: 99%
“…Despite the recent evolution of the epistemological trends discussed above, creativity research has seldom appreciated the extent to which distributed interaction properties play a role in creative processes (Kurtzberg and Amabile, 2001;Lebuda et al, 2016;Almaatouq et al, 2021). Instead, ideas are still most often thought to be born out of individual minds before they reach the world, and therefore others (Wheeler, 2018).…”
Section: Creativity As a Distributed Processmentioning
confidence: 99%